The Cellular Interactions of PEGylated Gold Nanoparticles: Effect of PEGylation on Cellular Uptake and Cytotoxicity. (24th February 2014) - Soenen, Stefaan J.; Manshian, Bella B.; Abdelmonem, Abuelmagd M.; Montenegro, José‐María; Tan, Sisareuth; Balcaen, Lieve; Vanhaecke, Frank; Brisson, Alain R.; Parak, Wolfgang J.; De Smedt, Stefaan C.; Braeckmans, Kevin
<x xml:space="preserve">Abstract</x> Poly(ethylene glycol) (PEG) is frequently used to coat various medical nanoparticles (NPs). As PEG is known to minimize NP interactions with biological specimens, the question remains whether PEGylated NPs are intrinsically less toxic or whether this is caused by reduced NP uptake. In the present work, the effect of gold NP PEGylation on uptake by three cell types is compared and evaluated the effect on cell viability, oxidative stress, cell morphology, and functionality using a multiparametric methodology. The data reveal that PEGylation affects cellular NP uptake in a cell‐type‐dependent manner and influences toxicity by different mechanisms. At similar intracellular NP numbers, PEGylated NPs are found to yield higher levels of cell death, mostly by induction of oxidative stress. These findings reveal that PEGylation significantly reduces NP uptake, but that at similar functional (= cell‐associated) NP levels, non‐PEGylated NPs are better tolerated by the cells.